Depression and chronic diseases among older adults: the moderating role of smoking - Yong, Kang Cheah; Syed Anera, Sharifah Nazeera; Omar, Mohd Azahadi; Abd Manaf, Noor Hazilah; Idris, Zera Zuryana (ScienceDirect, 2025)
Depression and chronic diseases often coexist. They possess negative impacts on health outcomes among older adults. The present study explores the associations between depression and chronic diseases, as well as the moderating role of smoking within a large sample of older adults. Cross-sectional data from the Malaysian National Health and Morbidity Survey 2018 were utilised. Probit models were used to assess parameters influencing the probability of experiencing depression. The moderating effect of smoking was examined by adding diabetes-smoking and hypertension-smoking interaction terms to the regression models. Results showed that older adults with diabetes and hypertension were more likely to experience depression compared to their non-diabetic and non-hypertensive counterparts. While smoking was not independently associated with depression, it moderated the relationship between diabetes and depression. However, the hypertension-depression relationship was not moderated by smoking. Other factors that were correlated with depression included gender, ethnicity, marital status, education, income, physical activity and body mass index (BMI). In conclusion, smoking played an important role in strengthening the relationship between depression and diabetes. Anti-depression policies should give particular consideration to diabetic older adults who smoked tobacco. Interventions to reduce the prevalence of depression should also take account of older adults’ demographic traits and lifestyles.